THE ECOLOGY OF ANOPHELES ARABIENSIS AND INSECTICIDE RESISTANCE/ SUSCEPTIBILITY STATUS IN KASSALA AREA, EASTERN SUDAN - Hamza, Asma Mahmoud; Himeidan, Yousif El-Safi; Adam, Ishag; El-Rayah, El-Amin (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
Objectives: The study was carried out to investigate the ecology of A. arabiensis and their susceptibility to insecticides in Kassala area, eastern Sudan. Methods: Both adult anopheline mosquitoes and immature stages were sampled monthly following the standard WHO procedures during the period November 2000 through January 2002. The susceptibility of A. arabiensis to insecticides was conducted using the WHO standard technique. Results: A. arabiensis was the main malaria vector; its density fluctuated throughout the year with  bimodal peaks during the rainy (6.1 females/room and 56.1 larvae/dip) and the cool dry seasons (4.8 females/room and 47.5 larvae/dip). The difference was not statistically significant ( P >0.05). An indication of partial aestivation of A. arabiensis to adapt the harsh environmental conditions of the dry season was confirmed in the area. Adult populations like to cluster around breeding sites in an area of less than 200 m. The susceptibility to DDT and fenitrothion was 88.3% and 100% respectively. Conclusion: A. arabiensis is the sole malaria vector in Kassala area and it was highly susceptible to the insecticides tested and these should be considered for malaria vector control in the area.